Multi-omics approaches for deciphering the complexity of traditional Chinese medicine syndromes in stroke: A systematic review - Liu, Tingting; Qin, Mingzhen; Xiong, Xuejiao; Lai, Xinxing; Gao, Ying (Frontiers in Pharmacology, 2022)
Background: Deciphering the biological basis of traditional Chinese medicine (TCM) syndromes in complex diseases is challenging. Rapid advances in multi-omics approaches provide new opportunities to unveil the biological basis of TCM syndromes. We intend to summarize the latest significant progress and highlight the crucial value of applying multi-omics approaches to reveal TCM syndromes of stroke in a new horizon. Methods: We systematically searched PubMed, EMBASE, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Periodical Database (VIP), Wanfang database and China Biology Medicine Database (SinoMed) for relevant studies from their inception to March 31, 2022, and conducted a comprehensive systematic review (PROSPERO registration number: CRD42021285922). Results: A total of 43 relevant studies were included in the final systematic review, genomics, transcriptomics, proteomics and metabolomics were all involved. Some gene polymorphisms, differential lncRNAs, mRNAs, miRNAs, proteins and metabolites may be associated with TCM syndromes of stroke. In addition, some studies conducted a preliminary exploration on the different diseases with the same TCM syndrome. The results showed that thioredoxin-dependent peroxidase reductase may be the specific marker protein of Liver-yang transforming into wind syndrome, and the network formed by mir-146b-5p, -199a-5p and 23 targeted mRNAs may be the biomarker of Blood-stasis syndrome. Conclusion: Multi-omics technologies have served as powerful tools to investigate the complexity of TCM syndromes and may hold the the promise of promoting the modernization of TCM as well as personalized medicine of TCM in stroke.